Logic and Semiotic Passportization of Numbers in Different Cultures - Vasko, Roman; Korolyova, Alla; Pakholok, Zinaida; Korolyov, Igor (Journal of History Culture and Art Research, 2020)
This article is a continuation of the discussion of a new idea about the need to compile a culturological passport of each number and its symbolic sacralization in different cultures, which was proposed for an interdisciplinary study in one of his works by the co-author R. Vasko “Semiotic and Culturological Passportization of Numeric Phraseosymbols”. The team of the article authors makes convincing arguments that the symbolic parameter should be the initial criterion for systematization of numbers in such a passport-calendar (a kind of database). The source of the symbolism of the number is, first of all, the mythology of different peoples of the world, which helps to reveal through quantitative characteristics the internal properties and qualities of various events. Taking into account the mythological and semiotic sacred parameter of the passportization data of modern numbers, it is proposed to consider numbers as a configuration of the symbolism of previous and subsequent signs, which undergo further transformation and, thus, receive a new sacred component in their mythopoetic meaning, characteristic of each national culture. A preliminary conclusion is made that the process of the number symbolization from one to thirteen in the mythopoetic traditions of different cultures reflects both the paradigmatics of the numerical series (i.e., its structure and properties of its members) and syntagmatic (i.e., functioning of numbers in mythopoetic and folklore texts).